Citizen Science to Communicate about Public Health Messages: The Reach of a Playful Online Survey on Sitting Time and Physical Activity. Issue 7 (7th June 2019) - De Cocker, Katrien; Chastin, Sebastien F.M.; De Bourdeaudhuij, Ilse; Imbo, Ineke; Stragier, Jeroen; Cardon, Greet
ABSTRACT: There is a lack of research on how to communicate public health guidelines. Citizen science (CS) has been an effective way to involve the public in research. This study analyses the reach of a well-established CS experiment, launched during an annual national science event, to understand if it could be used as communication strategy for public health issues. A short playful online survey contained tailored health-related messages associated to an "animal totem" profile, based on the combination of sitting and physical activity levels (koala: high sitting, low activity; gorilla: high sitting, high activity; zebra: low sitting, low activity; bee: low sitting, high activity). Tweets, radio interviews, radio and online advertisements, press articles, and a press conference were used to promote the CS experiment. Google Analytics and Facebook Graph API (application programming interface) (use and spread of experiment) and descriptive statistics (attributes of adults completing the experiment) were used. A total of 6, 246 adults completed the experiment, with a peak of views ( n = 5, 103) and completions ( n = 1, 209) a couple of days before the event. Completers were mostly female (65.8%), on average 37.5 years old, and had a healthy body mass index (23.8 kg/m 2 ). Nearly half (46.4%) had the most beneficial profile ("bee"), 26.5% had the least healthy profile ("koala"). CS as part of a national science event is a good platform for health communication as 1 in 1, 000 Flemish adults were reached. However, those completing the experiment were not representative of the general Flemish adult population and reported to be more physically active. Abbreviations: API: application programming interface; BMI: body mass index; CVD: cardiovascular disease; METs: metabolic equivalents